Dari E-WOM ke Pembelian: Menjelajahi Pengaruh Citra Merek, Kuantitas, dan Kredibilitas di GoFood - Muhammad Dafi Aswinda Nasution; Apsari Sugiat, Maria (Universitas Muhammadiyah Pontianak, 2026)
This study examines the influence of Electronic Word of Mouth (E-WOM) quantity and credibility on online purchase intention through the mediating role of brand image in the context of GoFood. A quantitative causal research design was employed with structured questionnaires distributed via Google Forms to 384 Indonesian GoFood users aged 18 years and above. Data were analyzed using Partial Least Squares Structural Equation Modeling via SmartPLS 4. Results indicate all six hypotheses are statistically supported. E-WOM quantity demonstrated the strongest effect on EWOM credibility, followed by E-WOM credibility on brand image, and brand image on purchase intention.